Pelatihan Progressive Muscle Relaxation untuk Mengurangi Stres pada Ibu Rumah Tangga - Apta Mylsidayu; Dinan Mitsalina; Ayu Purnama Wenly; Ramdan Pelana; Sukiri Sukiri (Universitas Baiturrahim, 2026)
Pramuka Island, the administrative center of the Thousand Islands Regency, faces various social and mental health challenges, particularly among housewives who are vulnerable to stress due to multiple burdens, fluctuating economic conditions, and limited psychosocial support. Progressive Muscle Relaxation (PMR) is a simple and practical relaxation technique that can be performed independently, making it a potential community-based strategy for stress management. This community service program aimed to provide PMR training for housewives on Pramuka Island to enhance their knowledge and skills in managing stress. The training was conducted on July 11, 2025, at SMAN 69 Jakarta with 12 participants. The activities consisted of pre-test, education, PMR practice, discussion, post-test, and evaluation. Results indicated a significant improvement in knowledge, with the mean score increasing from 61.7 (pre-test) to 85 (post-test), accompanied by a reduction in score variation among participants. All participants (100%) reported feeling more relaxed and being able to practice PMR independently, while the majority (91.7%) experienced reduced stress and expressed the intention to apply PMR in their daily lives. Overall, PMR training proved effective as a simple, low-cost, and relevant intervention to support the mental health of housewives. It is recommended for integration into community-based public health programs